Dextran based Polymeric Micelles as Carriers for Delivery of Hydrophobic Drugs - Mocanu, Georgeta; Nichifor, Marieta; Sacarescu, Liviu (Current Drug Delivery, 2017)
Background: The improvement of drugs bioavailability, especially of the hydrophobic ones, by using various nanoparticles is a very exciting field of the modern research. Objective: The applicability of nano-sized shell crosslinked micelles based on dextran as supports for controlled release of several hydrophobic drugs (nystatin, rifampicin, resveratrol, and curcumin) was investigated by in vitro drug loading/release experiments. Methods: The synthesized crosslinked micelles were loaded with drugs of various hydrophobicities and their retention/release behavior was followed by dialysis procedure. Results: Crosslinked micelles obtained from dextran with octadecyl end groups, with or without N-(2- hydroxypropyl)-N,N-dimethyl-N-benzylammonium chloride groups attached to the main dextran chains, could retain the drugs in amounts which increased with increasing drug hydrophobicity (water insolubility), as follows: 30-60 mg rifampicin/g, 70-100 mg nystatin/g, 120-144 mg resveratrol/g and 146-260 mg curcumin/g. The rate of drug release from the loaded micelles was also dependent on the drug hydrophobicity and was always slower than the free drug recovery. Antioxidant activity of curcumin and resveratrol released from the loaded micelles was preserved. Conclusion: The results highlighted the potential of the new nano-sized micelles as carriers for prolonged and controlled delivery of various hydrophobic drugs.
Keywords: micelles